1977
DOI: 10.1021/bi00639a015
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and amino-terminal sequence analysis of a new pancreatic trypsinogen of the African lungfish Protopterus aethiopicus

Abstract: The purification and characterization of three pancreatic trypsinogens A1, A2, and A3, from the African lungfish, Protopterus aethiopicus, is reported. These zymogens are activated by trypsin, by enterokinase, by an acid protease from Aspergillus oryzae, and by autoactivation. The three trypsinogens contain the same amino-terminal amino acid sequence, beginning with the activation peptide Leu-Pro-Leu-Glu-Asp-Asp-Lys-. Like the activation peptide of the previously characterized trypsinogen B [Reeck, G. R., & Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The unusual four aspartyl residues (Asp 4 ) preceding the cleavage bond Lys23-Ile24 (human trypsinogen numbering is used throughout the text) were found to be strictly conserved in trypsinogen activation peptides of pig (Charles et al 1963), sheep (Schyns, Bricteux-Gregoire, and Florkin 1969), and other mammals (e.g., Bricteux-Gregoire, Schyns, and Flokin 1972), including the human (Guy et al 1976(Guy et al , 1978. However, this is not always the case in nonmammalian vertebrates (e.g., de Haen, Walsh, and Neurath 1977). More recently, a comparative analysis of trypsinogen activation peptides suggested that there might be a progressive increase in selective pressure for such acidic residues during the course of vertebrate evolution (Roach et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The unusual four aspartyl residues (Asp 4 ) preceding the cleavage bond Lys23-Ile24 (human trypsinogen numbering is used throughout the text) were found to be strictly conserved in trypsinogen activation peptides of pig (Charles et al 1963), sheep (Schyns, Bricteux-Gregoire, and Florkin 1969), and other mammals (e.g., Bricteux-Gregoire, Schyns, and Flokin 1972), including the human (Guy et al 1976(Guy et al , 1978. However, this is not always the case in nonmammalian vertebrates (e.g., de Haen, Walsh, and Neurath 1977). More recently, a comparative analysis of trypsinogen activation peptides suggested that there might be a progressive increase in selective pressure for such acidic residues during the course of vertebrate evolution (Roach et al 1997).…”
Section: Introductionmentioning
confidence: 99%